Lost in a sea of words? Discourses of the Russian geopolitical thinking on the Arctic - Saarikoski, Leena (2014)
Kansainvälisen politiikan pro gradu -tutkielma: Tampereen yliopisto, Johtamiskorkeakoulu, 2011. This thesis focuses on the geopolitical thinking of the Russian Federation in the Arctic areas, especially as it pertains to the role of the modernization of the Russian economy and to the importance of the sea in world politics. The aim is to contribute to the better understanding of Russia’s arctic politics and to the different actors in Russia through using Critical Discourse Analysis to study Russian official and political discourses. Moreover the focus is to scrutinize, how Russian geopolitical thinking constructs the Arctic and how the Russian geopolitical thinking relates to John Agnew’s concept of modern geopolitical imagination. Russia’s politics towards the Arctic, or more precisely, the success of those policies will determine the future for this energy-dependent state. According to John Agnew’s concepts of modern geopolitical imagination, Russia views the Arctic as natural and sovereign part of the country. Russian geopolitical thinking in the north closely relates to the geopolitical and national interests of the country. Discourses traced in the research material were discourse on modernization, on country’s sovereign rights and on cooperation. In addition, the Arctic appears to be the strategic treasure trove for the country, which secures the future economic growth and sustainable stability. Simultaneously, the political leaders have often emphasized the demand for the modernization and the need to get rid of the energy revenues as a fundamental guarantee of the development of the country. Overall, the Arctic has served as a useful identity-building project, especially as a platform to reinforce a great power mentality.